Political economy of development in India - "Bardhan, Pranab" (Oxford, 1984)
In this book Bardhan examines the political and social constraints on Indian development. In the newly added epilogue Bardhan comments on the process of liberalization in the 1990 s and examines the feasibility of the exercise in the light of ground realities.
Keywords: India-Economic conditions-1947